2019
DOI: 10.3934/publichealth.2019.4.600
|View full text |Cite
|
Sign up to set email alerts
|

Social and cultural determinants of health; understanding the persisting Alcohol Use Disorder (AUD) in the rural populations in central Kenya

Abstract: Excessive alcohol use is a significant public health problem globally. Alcohol use typically begins in adolescence or early adult life, and effective prevention strategies focused on this age group are needed to avoid development of Alcohol Use Disorder (AUD). AUD is a worldwide problem resulting in millions of deaths, including hundreds of thousands of young lives lost. It is not only a causal factor in many diseases, but also a precursor to injury and violence. Furthermore, its' negative impacts can spread t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In regards to the opinion on whether alcohol helps relieve stress, 50.32% indicated that they started taking alcohol after the stressful experiences while 49.68% did not start taking alcohol as a result of the experiences above. This is consistent with a study done by Mindigo and others which noted that beliefs and perceptions of experiences with alcohol may perpetuate future alcohol-related expectancies (Mindigo et al,2019).…”
Section: Multivariate Analysis For the Psychosocial Factors Associate...supporting
confidence: 92%
“…In regards to the opinion on whether alcohol helps relieve stress, 50.32% indicated that they started taking alcohol after the stressful experiences while 49.68% did not start taking alcohol as a result of the experiences above. This is consistent with a study done by Mindigo and others which noted that beliefs and perceptions of experiences with alcohol may perpetuate future alcohol-related expectancies (Mindigo et al,2019).…”
Section: Multivariate Analysis For the Psychosocial Factors Associate...supporting
confidence: 92%
“…Alcohol use, was associated with several socio-demographic factors including being male [50,112,114,140,158,168,182,191], being unemployed [114], being self-employed [97], having a lower socio-economic status (SES) [128], being single or separated, living in larger households [97], having a family member struggling with alcohol use, and alcohol being brewed in the home [143]. Alcohol use was linked to various health factors including glucose intolerance [81], poor cardiovascular risk factor control [111], having a diagnosis of diabetes mellitus [134], hypertension [112,139], default from tuberculosis (TB) treatment [148], depression [113], psychological Intimate Partner Violence (IPV) [205], tobacco use [182,205], and increased risk of esophageal cancer [137,179].…”
Section: Plos Onementioning
confidence: 99%